2019
DOI: 10.1055/a-1033-7524
|View full text |Cite
|
Sign up to set email alerts
|

Time-Lag Between Symptom Onset and Diagnosis of Subacute Thyroiditis – How to Avoid the Delay of Diagnosis and Unnecessary Overuse of Antibiotics

Abstract: Clinical symptoms of subacute thyroiditis (SAT) may be misleading and the proper diagnosis is significantly delayed, and many unnecessary therapeutic methods are used, including application of antibiotics. The purpose of the study is to analyze the reasons and frequency of delayed SAT diagnosis and unnecessary antibiotic treatment and to propose a simple algorithm to facilitate the diagnosis and prevent antibiotic abuse. Sixty-four SAT patients were divided into groups depending on the period of time from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
(32 reference statements)
1
14
1
Order By: Relevance
“…In the literature, recent studies have focused on the diagnosis and treatment modalities of SAT. The delays in the prediagnosis period of the disease and its consequences have been presented in only one recent study [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, recent studies have focused on the diagnosis and treatment modalities of SAT. The delays in the prediagnosis period of the disease and its consequences have been presented in only one recent study [12].…”
Section: Discussionmentioning
confidence: 99%
“…The prediagnosis period was prolonged up to 70 days in some patients. Also, Stasiak et al [12] reported a delay of >2 weeks in SAT diagnosis in 73% of 64 patients. The pain radiating up to the ear/jaw was observed in 71% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subacute thyroiditis is a rare disease but its incidence is increasing. Many clinical symptoms of SAT are not characteristic, and diagnosis is often delayed, with many previous misdiagnoses and mistreatments being reported [24]. The data in the literature indicate that the occurrence of SAT is associated with genetic predispositions encoded in the sixth chromosome fragment responsible for the HLA tissue compatibility antigen system.…”
Section: Discussionmentioning
confidence: 99%